Characterising the extent and nature of digital food and beverage marketing in Singapore: a descriptive study - Xin Hui Chua; Clare Whitton; Stefanie Vandevijvere; Bridget Kelly; Rob M van Dam; Salome A Rebello (Public Health Nutrition)
Abstract